THE ENGLISH TEACHERS’ EXPERIENCES IN APPLYING TEACHING STRATEGIES DURING COVID-19 - HARYANA, LIA; HARDIYANTI, SRI; YUDANINGRUM, PUSPITA (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
Knowing the teaching strategy is very important in the teaching and learning process because it dramatically influences the students' outcomes. Many studies on teaching strategies have been done in many parts of the world. However, the studies on teaching strategies in the pandemic era applied by the teachers in a reputable school in Indonesia are rarely discussed. Thus, this research aims to explore a reputable school's teachers' experiences in applying strategies during covid-19. There were three senior high school teachers from one of the reputable schools in Bengkulu who participated in this research. This research adapted a case study design by using a semi-structured interview as the research instrument. The interview data were recorded, transcribed, and coded into several themes based on the focus of this research. The result showed that the teachers tended to use the same materials, such as books from the government and materials from the internet. In addition, the teachers dominantly use zoom meetings for the teaching media. Meanwhile, they had their preferences on the teaching strategies. Generally, the teachers prefer to implement online discussion, computer-based learning exercises, online collaboration projects, online lectures, independent study, and online learning using social networking as the teaching strategies. The result of this study can be used as a guideline for teachers from other schools in implementing the teaching strategies, especially in online teaching.